High-energy ions from Nd:YAG laser ablation of tin microdroplets: comparison between experiment and a single-fluid hydrodynamic model. (12th October 2021) - Hemminga, D J; Poirier, L; Basko, M M; Hoekstra, R; Ubachs, W; Versolato, O O; Sheil, J
Abstract: We present the results of a joint experimental and theoretical study of plasma expansion arising from Nd:YAG laser ablation (laser wavelength λ = 1.064 μ m) of tin microdroplets in the context of extreme ultraviolet lithography. Measurements of the ion energy distribution reveal a near-plateau in the distribution for kinetic energies in the range 0.03–1 keV and a peak near 2 keV followed by a sharp fall-off in the distribution for energies above 2 keV. Charge-state resolved measurements attribute this peak to the existence of peaks centered near 2 keV in the Sn 3+ –Sn 8+ ion energy distributions. To better understand the physical processes governing the shape of the ion energy distribution, we have modelled the laser-droplet interaction and subsequent plasma expansion using two-dimensional radiation hydrodynamic simulations. We find excellent agreement between the simulated ion energy distribution and the measurements both in terms of the shape of the distribution and the absolute number of detected ions. We attribute a peak in the distribution near 2 keV to a quasi-spherical expanding shell formed at early times in the expansion.